ANALISIS PENGGUNAAN ALAT EVALUASI PADA MATA PELAJARAN AKUNTANSI KELAS X PROGRAM KEAHLIAN AKUNTANSI DI SMK NEGERI 1 LAMONGAN - DWI MEI INTAN SARI (Jurnal Pendidikan Akuntansi (JPAK), 2013)
The study purpose to determine the types of evaluation tool in SMK Negeri 1 Lamongan and the reasons teachers choose the evaluation tool, determine the feasibility of the evaluation tool used by the teacher in the learning process and evaluation activities for the current attitudes and study the response of students to the evaluation tool used This study uses a descriptive research method research with quantitative approach.. The results showed that the evaluation tools in SMK Negeri 1 Lamongan a qualitative evaluation tool is very feasible and quantitatively that only the matter of daily tests competency standards process inventory cards have a value of: validity, reliability, level of difficulty and discrimination power is low. Students 'attitudes when executing daily tests are very good and students respond very well to the daily tests and students' response to good evaluation tool. Keyword: Evaluation Tool